A key to Meistera (Zingiberaceae: Alpinioideae) in Cambodia, Laos and Vietnam, with a description of a new species, M. muriformis - Leong-Škorničková, Jana; Bình, Nguyễn Quốc; Đăng, Trần Hữu; Záveská, Eliška; Quang, Bùi Hồng; Bình, Trần Đức; Ye, Xing-Er; Nguyen, Khang Sinh; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Nuraliev, Maxim S. (Phytotaxa, 2023)
Meistera muriformis (Zingiberaceae: Alpinioideae), a new species from southern Vietnam is described and illustrated. The description is accompanied by additional notes on etymology, ecology and phenology, distribution, and preliminary IUCN assessment. Notes on differences from morphologically similar congeners are provided. The new species is diagnosed from its morphologically closest species, Meistera stephanocolea, by prominently reticulate leaf sheaths, open flower type and small anther crest with no prominent lobes. The novelty brings the total number of species of Meistera in Cambodia, Laos and Vietnam to 15. Morphological diversity and distribution of Meistera in these countries are briefly summarised, and an identification key is provided.